2020
DOI: 10.1093/infdis/jiaa185
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Seasonal Coronaviruses: Establishing the Context for the Emergence of Coronavirus Disease 2019

Abstract: Public health preparedness for coronavirus (CoV) disease 2019 (COVID-19) is challenging in the absence of setting-specific epidemiological data. Here we describe the epidemiology of seasonal CoVs (sCoVs) and other cocirculating viruses in the West of Scotland, United Kingdom. We analyzed routine diagnostic data for >70 000 episodes of respiratory illness tested molecularly for multiple respiratory viruses between 2005 and 2017. Statistical associations with patient age and sex differed between CoV-229E,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
198
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(218 citation statements)
references
References 35 publications
15
198
0
5
Order By: Relevance
“…Six other coronaviruses are known to infect human. Four of them are endemically transmitted 5 and cause common cold (OC43, HKU1, 229E and NL63), while SARS-CoV (defined from now as SARS-CoV-1) and MERS-CoV have caused limited epidemics of severe pneumonia 6 . All of them trigger antibody and T cell responses in infected patients: however, antibody levels appear to wane relatively quicker than T cells.…”
Section: Main Textmentioning
confidence: 99%
“…Six other coronaviruses are known to infect human. Four of them are endemically transmitted 5 and cause common cold (OC43, HKU1, 229E and NL63), while SARS-CoV (defined from now as SARS-CoV-1) and MERS-CoV have caused limited epidemics of severe pneumonia 6 . All of them trigger antibody and T cell responses in infected patients: however, antibody levels appear to wane relatively quicker than T cells.…”
Section: Main Textmentioning
confidence: 99%
“…Cross-reactivity among betacoronaviruses has also been reported in polyclonal sera (21,22). Human coronavirus OC43, discovered in the 1960s, is one of the major betacoronaviruses that cause common colds in the community (23,24), and severe respiratory infections in elderly and immunocompromised individuals (22,25). Epidemiologic surveys reveal that OC43 infection can occur in early childhood, and that OC43 seropositivity reaches nearly 90% in adults (26,27).…”
Section: Cross-reactivity and Somatic Hypermutationmentioning
confidence: 99%
“…Recovered plasma is usually obtained from elder donors. A trend towards increasing probability of hCoV-229E infections with age was detected in the Scottish [3] and US [4] population. Furthermore, higher hCoV-229E specific nAb titers were found in older study participants (60-85 years) compared to younger ones (21-40 years) [10].…”
Section: Discussionmentioning
confidence: 86%
“…The virus belongs to the Coronaviridae family of viruses which contains several species of importance for human health. The human coronaviruses (hCoVs) 229E, NL63, OC43, and HKU1 are in circulation as seasonal respiratory viruses that mostly cause self-limiting and mild infections but which can also lead to pneumonia and bronchiolitis [2][3][4] Due to the widespread and long-term circulation of hCoVs, and the pooling of plasma from thousands of donors for every lot of IVIG, it was shown that IVIGs contain significant levels of hCoV nAb levels, as was shown for example for hCoV-NL63 [5]. Whether these hCoV antibodies cross-react with or even neutralize the related SARS-CoV-2 has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%